Publication Categories in Toxicologic Pathology. (July 2021) - Boyle, Molly H.; Bennet, Bindu; Colman, Karyn; Frisk, Anna-Lena; Garcia, Begonya; Houle, Christopher D.; Romeike, Annette; Sura, Radhakrishna; Werner, Jonathan; Elmore, Susan A.
Toxicologic Pathology is the official journal of the Society of Toxicologic Pathology (STP), the British Society of Toxicological Pathology, and the European STP (ESTP). Toxicologic Pathology publishes articles related to topics in various aspects of toxicologic pathology such as anatomic pathology, clinical pathology, experimental pathology, and biomarker research. Publications include society-endorsed Best Practice/Position and Points to Consider publications and ESTP Expert Workshop articles that are relevant to toxicologic pathology and scientific regulatory processes, Opinion articles under the banner of the STP Toxicologic Pathology Forum, Original Articles, Review Articles (unsolicited/contributed, mini, and invited), Brief Communications, Letters to the Editor, Meeting Reports, and Book Reviews. This article provides details on the various publication categories in Toxicologic Pathology and will serve as a reference for authors and readers.